Pertanggungjawaban Pidana Koki terhadap Konsumen yang Mengalami Keracunan Makanan (Studi Kasus: Kasus Keracunan Makanan di Restoran Cepat Saji X Tahun 2021) - Akbar, Muhammad; Rosando, Abraham Ferry (Journal Evidence Of Law, 2025)
Food poisoning in restaurants is still a serious problem in the culinary industry, where the responsibility of chefs in maintaining food hygiene and safety plays an important role. This study aims to analyze the criminal liability of chefs towards consumers who experience food poisoning, using case studies of incidents in fast food restaurants in the last five years. The research method used is a qualitative approach with case studies and legal document analysis as well as in-depth interviews with several related parties, including chefs, restaurant management, and health services. The results of the study indicate that chefs' negligence in maintaining food hygiene standards can cause significant health risks to consumers, and in developed countries, the criminal liability of chefs is strictly regulated. In Indonesia, regulations on the criminal liability of chefs in cases of food poisoning are not yet clear, so this responsibility is often divided between chefs and restaurant management. The role of health services in conducting inspections and education is also very important in ensuring that hygiene standards are met. More specific regulations and strict sanctions are needed to improve compliance with hygiene standards in restaurants. This study concludes that the criminal liability of chefs in cases of food poisoning needs to be regulated in more detail in Indonesia. With clear regulations and consistent supervision from the health department, it is hoped that food poisoning incidents can be minimized, so that consumer safety can be more assured.